THE ROLE OF DIGITAL MARKETING IN FORMING ECOLOGICAL AWARENESS OF CONSUMERS (Marketing Journal, 2025)
The article examines the role of digital marketing in shaping consumersʼ environmental awareness. Based on content analysis and comparative approaches, it discusses the effectiveness of social media, mobile applications, and interactive advertising in prom oting ecological values. The findings indicate that digital platforms significantly influence consumersʼ ecological attitudes and behavioral changes. The study also highlights the social importance of green marketing and the role of brands in fostering env ironmental culture through digital strategies. 189
Keywords: digital marketing; environmental awareness; consumer behavior; sustainable development; social media; interactive content; ecological values; eco - friendly products; digital strategy; environmental responsibility; marketing communications; mobile applicati ons